Research on the Philosophy of Science Oriented to Deep Learning under the Ethical Dilemma - Jie Zhou; Ratna Roshida Ab. Razak (International Journal of Intelligent Systems and Applications in Engineering, 2022)
The rapid growth in technology has resulted in the technical up-gradation of works in every field. In this study, we are going to research the philosophy of science-oriented to deep learning under the ethical dilemma The philosophy of science is concerned with the value and use of scientific knowledge and its underlying assumptions, techniques, and implications. An ethical dilemma arises when a person is forced to choose between two courses of action, neither of which is morally permissible. Random Forest Algorithm is used in this research to perform regression and classification tasks. It is found that the Random Forest Algorithm outperforms other algorithms in classification problems.